50 & 25 Years Ago. - Neuhold, Erich (Computer (00189162), 2022)
Application of Digital Computers to Air Traffic Control in the United States; Howard J. Kirshner (p. 14): "Radar-oriented tracking and alphanumeric display systems using digital computers are just now emerging as the key data processing tool in air traffic control, although the Great Falls Center, using air defense computer and display facilities, has been in operation since 1963." (p. 15) "Aircraft operations in the United States are conducted under two forms of ATC procedures. The first procedure is called Visual Flight Rules, or VFR, and the second, Instrument Flight Rules, or IFR. ... Under Visual Flight Rules, it is the responsibility of the aircraft's pilot to maintain adequate separation from other aircraft. ... The ground-based ATC system is responsible for providing separation among aircraft flying under IFR, although in clear weather the pilot also has a responsibility to see and avoid other traffic, since not all aircraft in most segments of low-altitude airspace will be under control of the ground system." (p. 16) "At 61 locations having radars and beacons, the computer-based Advanced Radar Terminal System (ARTS) is being deployed." [Editor's note: The article describes in detail the use of computers to analyze and display information that is captured by radar and beacon facilities. The impression is that none of these systems is yet (1972) ready for use but will become available soon.]